Examining the drivers of the imbalance price: Insights from the balancing mechanism in the United Kingdom - Jinke Li (Journal of Environmental Management, 2024)
The increasing integration of renewable energy sources in the UK electricity sector has posed challenges to the stability of the system, leading to a sharp rise in the costs of balancing services. This study analyses half-hourly data from January 2017 to December 2023 to examine the factors determining the imbalance price in the UK's balancing mechanism, with particular focus on the sharp price increases in 2021–2022. Employing a Generalised Additive Model (GAM) to account for non-linear relationships, the analysis finds that the imbalance price is positively affected by the net imbalance volume (demand-side factor) and negatively impacted by the de-rated margin (supply-side factor). The wholesale electricity price, however, is identified as the dominant factor driving both the mean and volatility of the imbalance price during 2021–2022. These findings suggest that the balancing mechanism is functioning effectively and that a reduction in the wholesale price would lead to a lower imbalance price and thus lower costs of balancing services.